Clinical characteristics and outcomes of primary immunodeficiencies in thai children: An 18-year experience from a tertiary care center - P. Benjasupattananan (2018)
Abstracts: Introduction: Early diagnosis and treatment are keys to improve survival of patients with primary immunodeficiency diseases (PID). The clinical characteristics of these patients in Thailand were not well defined. Objective: This study aimed to determine the clinical characteristics and outcomes of patients with PID in Thailand. Methods: Medical records of PID patients in the past 18 years were reviewed. Results: Sixty-seven children were registered. Antibody deficiencies were the most common PID (52.2%), followed by combined T cell and B cell immunodeficiencies (25.4%), other well-defined immunodeficiency syndromes (11.9%), and phagocytic defects (10.4%). The most common presentations of antibody deficiencies, combined T cell and B cell immunodeficiencies, and phagocytic defects were infection in the upper respiratory tract (74.3%), gastrointestinal tract (82.4%), and skin (85.7%), respectively. The highest mortality rate (52.9%) was found in severe combined immunodeficiency. Conclusion: These results provide clinical features of PID in Thailand. Knowing these features will lead to prompt diagnosis and appropriate management. © 2009 Springer Science+Business Media, LLC.